Ovicidal and larvicidal activity of extracts from medicinal-plants against Haemonchus contortus - Váradyová, Zora; Pisarčíková, Jana; Babják, Michal; Hodges, Alfred; Mravčáková, Dominika; Kišidayová, Svetlana; Königová, Alžbeta; Vadlejch, Jaroslav; Várady, Marián (Experimental parasitology, 2018)
The use of medicinal plants (MP) containing bioactive compounds is an alternative strategy to control of parasitic nematode of small ruminants Haemonchus contortus at various stages of their life cycle. The aims of this study were to determine the in vitro anthelmintic activity of both aqueous and methanolic extracts from 13 medicinal plants typical for Central Europe, and to determine quantity of selected plant secondary metabolites (PSMs) in the methanolic extracts. In vitro egg hatch test and larval development tests were conducted to determine the possible anthelmintic effects of methanolic and aqueous extracts of the roots of Althaea officinalis L., Petasites hybridus L. and Inula helenium L.; flowers of Malva sylvestris L. and Chamomilla recutita L.; leaves of Plantago lanceolata L. and Rosmarinus officinalis L.; seeds of Foeniculum vulgare Mill. and stems of Solidago virgaurea L., Fumaria officinalis L., Hyssopus officinalis L., Melisa officinalis L. and Artemisia absinthium L. on eggs and larvae of H. contortus. Ultra-performance liquid chromatography and tandem mass spectroscopy was used for quantifying six PSMs: gallic acid (GA), rutin (RU), diosmin (DI), hesperidin (HE), quercetin (QU) and kaempferol (KA). RU content of the most effective methanolic extracts was in the order: M. sylvestris (9.33 mg/g DM) > A. absinthium (6.10 mg/g DM) > C. recutita (0.42 mg/g DM). The highest concentration of QU (44.8 mg/g DM) and KA (6.59 mg/g DM) were detected in stems of F. officinalis comparing to the other evaluated plants. The most significant (p < 0.05) anthelmintic effects exhibited methanolic extracts of A. absinthium in both in vitro tests (i.e., egg hatch test and larval development test). Additionally, only two methanolic extracts of C. recutita and M. sylvestris were comparable to activity of A. absinthium using the larval development test. Wider spectrum of aqueous extracts exhibited stronger ovicidal activity in comparison to methanolic extracts. The similar trend was observed in evaluating of larvicidal activity of aqueous and methanolic plant extracts.
Keywords: Sheep; Plant Extracts; Chromatography, Liquid; Kaempferols; feces; Tandem Mass Spectrometry; Artemisia absinthium; larva; Plants, Medicinal; Haemonchus contortus; Malva; quercetin; UPLC/MS/MS; zvířata; Haemonchus; Europe; In vitro tests; rostlinné extrakty; Anthelmintics; Anthelmintic activity; Feces; tandemová hmotnostní spektrometrie; Bioactive compounds; chromatografie kapalinová; Ovum; anthelmintika; Fumaria; ovum; Matricaria; Larva; kempferoly; Animals; léčivé rostliny; Evropa; ovce; Quercetin